Elastomeric Pump Infusion Failures Caused by Inadequate Luer Lock Connector Engagement to Needleless Connectors. Issue 5 (September 2021) - Lui, Gough Yumu; Dickson, Hugh G.; West, Dana; Alexandrou, Evan; Malone, Matthew; Breen, Paul P.
Abstract : Needleless connectors are used widely across all types of vascular access devices and provide safe, needleless administration of intravenous fluids and medications. An analysis of patients from an outpatient parenteral antimicrobial therapy program is presented in which elastomeric pumps had failed to flow due to incomplete tightening of Luer lock needleless connections. An alert was issued to community nursing staff responsible for daily elastomeric pump changes to ensure that needleless connectors were properly checked for full tightening. The frequency of failure of flow events before and after the alert was reviewed. Force and torque profiles required to activate the internal mechanism of connectors were measured in the 4 most frequently used needleless connectors in the outpatient parenteral antimicrobial therapy program. The degree of torque and force required to activate the different needleless connectors varied and was identified as a factor contributing to inadequate connection with the elastomeric pump and consequent failure of flow. Repeated feedback to nursing staff over the study period about the force and torque required for needleless connector flow activation resulted in a highly significant decrease in the rate of failure of flow events per elastomeric pump from a rate of 0.0147 events per elastomeric pump per year in the last 3 months of 2018 to 0.0003 in the first 6 months of 2020 (difference = 0.0144 [CI, 0.0097–0.02]; P < .0001).